Conquering versus democratizing the state: political Islamists and fourth wave democratization in Turkey and Tunisia. Issue 6 (19th September 2017) - Somer, Murat
ABSTRACT: What do we learn from Turkey and Tunisia regarding the relationship between political Islamism and democratization? Variables identified by current research such as autonomy, "moderation", and cooperation with secular actors can cut both ways depending on various political-institutional conditions and prerogatives. Particularly, the article argues that preoccupation with "conquering the state from within as opposed to democratizing it" has been a key priority and intervening variable undermining the democratizing potential of the main Turkish and Tunisian political Islamic actors – primarily the AKP and Ennahda. These actors have prioritized acceptance by and ownership of their respective nation states over other goals and strategies, such as revolutionary takeover or Islamization of the state and confrontations with state elites. This has led to a relative neglect of designing and building institutions, whether for Islamic or democratic transformation. Hence, while contributing to democratization at various stages, these actors have a predisposition to adopt and regenerate, reframe and at times augment the authoritarian properties of their states. Research should ask how secular and religious actors can agree on institutions of vertical and horizontal state accountability that would help to address the past and present sources of the interest of political Islamists in conquering rather than democratizing the state.